Dalit Participation in Total Sanitation Campaign with Special Reference to Satara District in Maharashtra. Issue 2 (November 2017) - Jamdade, Pravin; Jungari, Suresh; Thakur, Mahesh
Development cannot be achieved without the participation of people from all segments of society. It is a process that requires collective action for social transformation or social change in the socio-economic and political lives of the people. The Total Sanitation Campaign (TSC) is one of the major programmes in India to promote sanitation and hygiene. The article is an attempt made to understanding the Dalit population's participation in the total sanitation programme. The field visits in six villages reveal that illiterate 20 per cent respondents did not participate in the decision-making process. Gram panchayat has not given equal opportunity for participation to Dalit women in the planning process of the campaign activities. Educated people are more likely to get the opportunity for participation in planning and implementation of the scheme. Villages, even gram panchayats, have not conducted any awareness campaign to disseminate the information of the Campaign among Dalit and rural masses.